SAKRALISTIK GUNUNG MERBABU: MENELUSURI TEMPAT-TEMPAT SAKRAL MELALUI LENSA ANTROPOLINGUISTIK - Dias Suci Rahmawati; Dany Ardhian (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Mount Merbabu has a number of places that are considered sacred by the surrounding community. To understand more about these sacred places, a comprehensive understanding is needed, including how a place can be considered sacred on Mount Merbabu via Selo ascent and how the practices and perceptions of the local community towards these places. The purpose of this study is to explore and describe the sacredness factors of sacred places on Mount Merbabu Via Selo and describe the practices and perceptions of the local community. This research took place in Mount Merbabu via Selo ascent, Central Java, Indonesia. The data in this study are in the form of various information related to sacred places on Mount Merbabu. The source of data in this research is informants who are native Selo residents. This research is descriptive qualitative type. Data were collected through interviews, and studied using the theory of sacredness and perception. The results showed that symbol, myths, traditions, and also prohibitions underlie the sacredness of a place. Furthermore, the seven sacred places are able to create complex dynamics in the lives of the surrounding community.